Dendritic spine dynamics in associative memory: A comprehensive review. Issue 5 (31st March 2023) - Guo, Hongling; Ali, Tahir; Que, Jianyu; Zhou, Yanmei; Bai, Yang
Abstract: Associative learning and memory are fundamental behavioral processes through which organisms adapt to complex environments. Associative memory involves long‐lasting changes in synaptic plasticity. Dendritic spines are tiny protrusions from the dendritic shaft of principal neurons, providing the structural basis for synaptic plasticity and brain networks in response to external stimuli. Mounting evidence indicates that dendritic spine dynamics are crucial in different associative memory phases, including acquisition, consolidation, and reconsolidation. Causally bridging dendritic spine dynamics and associative memory is still limited by the suitable tools to measure and control spine dynamics in vivo under behaviorally relevant conditions. Here, we review data providing evidence for the remodeling of dendritic spines during associative memory processing and outline open questions. Abstract : Associative learning and memory are essential for the survival of animals. Changes in the structure and function of dendritic spines (dendritic spine dynamics) play key roles in associative learning and memory, which are regulated by numerous molecular mechanisms.